Effect of remote ischemic preconditioning in the expression of IL-6 and IL-10 in a rat model of liver ischemia-reperfusion injury - Guimarães Filho,Marco Antonio Correa (2015)
PURPOSE: To study the effect of remote ischemic preconditioning (RIPC) in ischemia-reperfusion (I/R) liver injury and in the expression of IL-6 and IL-10 in a rat model. METHODS: Thirty-six male rats were divided in three groups: Sham; I/R injury, a 45 minutes lobar liver ischemia and reperfusion; and RIPC, six cycles of four minutes of ischemia and four minutes of reperfusion on the right hindlimb followed by a 45 minutes lobar liver ischemia and reperfusion. Tissue and blood samples were collected after 1h and 3h of reperfusion for histopathological study, plasma cytokines and alanine aminotransferase (ALT) measurement. RESULTS: The histopathological study demonstrated a significant reduction in liver necrosis in the RIPC group (p<0,001). The ALT levels were also significant lower in the RIPC group (p<0.01). The cytokines assessment showed that IL-6 levels were increased in the RIPC group after 1h of reperfusion, in comparison to the I/R group (p<0.05). Interleukin-10 levels in RIPC groups did not differ significantly from I/R group. CONCLUSIONS: Remote ischemic preconditioning is effective in decreasing liver necrosis in a rat model of ischemia-reperfusion. The IL-6 expression is up-regulated and peaked at 60 min of reperfusion. There was no difference in IL-10 expression between the groups.